PRINSIP KESANTUNAN BERBAHASA DALAM EDITORIAL SURAT KABAR HARIAN TRIBUN PEKANBARU (KAJIAN PRAGMATIK) - Lestari, Sri; Asnawi, Asnawi (Adabiyyāt: Jurnal Bahasa dan Sastra, 2020)
Politeness is something that can show a person's ethics or manners in communication, not only in spoken but also in written language. One of the written communication media is newspapers that are always published with editorials, for example, the Tribun Pekanbaru. This newspaper is the object of this study, with the sample taken in the September 2020 editions. This study focuses on one research question: how are the principles of politeness applied in the editorial of the daily newspaper Tribun Pekanbaru? With a pragmatic approach, this study utilizes Leech’s politeness principles maxims. This is a descriptive study that aims not only to collect data and information, but also to describe, analyze, interpret, and conclude the politeness principles contained in the editorial of the daily newspaper Tribun Pekanbaru. This research is expected to increase the reader's knowledge about pragmatic studies, especially regarding aspects of linguistic politeness. The results of the study showed that from 23 editorials in the September 2020 editions of the Tribun Pekanbaru newspaper, 18 data of either compliance or violations of maxims in the principle of politeness in language.